2021
DOI: 10.3390/ijerph18168662
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Treatments for Personal Protective Equipment: Experimental Microbiological Investigations and Perspectives for the Enhancement of Antimicrobial Activity by Micrometric TiO2

Abstract: The COVID-19 pandemic has led to countries enforcing the use of facial masks to prevent contagion. However, acquisition, reuse, and disposal of personal protective equipment (PPE) has generated problems, in regard to the safety of individuals and environmental sustainability. Effective strategies to reprocess and disinfect PPE are needed to improve the efficacy and durability of this equipment and to reduce waste load. Thus, the addition of photocatalytic materials to these materials, combined with light expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Based on the 2019 World Health Organization prediction, the mortality of infectionrelated diseases will be similar to that of cancer by 2050. 11,12,[261][262][263] Modified TiO 2 NPs have provided some promising candidates for controlling virus-type infections, supported by recent worthwhile publications in this frontier area of nanomedicine.…”
Section: Antiviralmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on the 2019 World Health Organization prediction, the mortality of infectionrelated diseases will be similar to that of cancer by 2050. 11,12,[261][262][263] Modified TiO 2 NPs have provided some promising candidates for controlling virus-type infections, supported by recent worthwhile publications in this frontier area of nanomedicine.…”
Section: Antiviralmentioning
confidence: 94%
“…Regarding their industrial importance, the global market size of TiO 2 NPs was estimated to be $1.1 billion in 2021, and forecasted to have a compound annual growth rate of 6.5% until 2026, with annual production predicted to reach 2.5 million tons by 2025. 5,6 In the biomedical fields, TiO 2 NPs are frequently studied for photodynamic therapy, 1,7 drug delivery, 8 antimicrobial applications, 3,[9][10][11][12] biosensors, 13 and tissue engineering. 14 For these applications, an appropriate surface modification of TiO 2 NPs is required to improve their physicochemical properties and biological effectiveness and, more importantly, decrease their potential toxicity in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that increasing particle contact with the bacteria enhanced the disinfection process and that excess TiO 2 might not enhance the antibacterial effect 51 . In a similar study, Margarucci et al 21 reported a significant reduction in the microbial load (over 90%) in facemasks using both E. coli and S. aureus bacteria within less than 1 h.…”
Section: Discussionmentioning
confidence: 79%
“…The filtering efficiency of face masks varies from one to another depending on the density of the face mask material 20 . With the continuous use of face masks without regular exchange, improper washing can potentially contaminate surfaces, as temperature and humidity induce moisture and hence microbial colonization; in addition, improper use may lead to the risk of pathogen spreading 21 25 . The disposal of face masks has led to an enormous increase in waste, which is classified as “hazardous with infectious risk”, and face masks are disposed of as biological hazards 26 .…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 has a strong oxidation capacity, good chemical stability, non-toxic, cheap and other excellent characteristics [57] . It is the most widely studied photocatalyst and can be used to inactivate a variety of viruses [ 98 , 99 ]. Metal-free photocatalysts include carbon nanotubes, graphene oxide and g-C3N4, which have stable physical and chemical properties, good electrical conductivity, hydrophobicity, and strong antibacterial activity [58] .…”
Section: Decontamination and Reuse Of Masksmentioning
confidence: 99%